Oxidation behavior of γ-TiAl based alloys at 900°C in air. (3rd May 2016) - Zhao, L.; Zhang, Y.; Zhu, Y.; Lin, J.; Ren, Z.
Abstract: The growth mechanisms of the oxide scales of Ti-50Al and Ti-45Al-8Nb (at%) alloys at 900°C in air were investigated. The results revealed that the oxidation of γ-TiAl alloys during experiments was divided into four stages. The Ti-50Al alloy showed severe spallation after 3 h of oxidation. Nb addition to γ-TiAl alloys could improve the oxidation resistance effectively. The oxide scale growth was much slower and every oxide layer was more chemically uniform and homogeneous with Nb addition. The Ti-45Al-8Nb alloy showed no spallation even after 100 h of oxidation.